2022
DOI: 10.13057/biodiv/d230814
|View full text |Cite
|
Sign up to set email alerts
|

New data on the vertical distribution of nematode communities in mountain ecosystems of Mount Zarafshan, Uzbekistan

Abstract: Abstract. Narzullayev SB. 2022. New data on the vertical distribution of nematode communities in mountain ecosystems of Mount Zarafshan, Uzbekistan. Biodiversitas 23: 3967-3975. New data on the vertical distribution of nematode communities in mountain ecosystems (Mount Zarafshan, Uzbekistan) is the first study on the variation of nematode species and ecological groups in Central Asia depending on altitude gradients. The study's primary purpose was to study the nematode fauna of perennial plants in the highland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Studies in the Zarafshan Valley so far have reported only one species of RKN (M. hapla) (Narzullayev, 2022). In these studies, the identification of nematode species was based solely on morphometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the Zarafshan Valley so far have reported only one species of RKN (M. hapla) (Narzullayev, 2022). In these studies, the identification of nematode species was based solely on morphometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The biological diversity of pastures of the arid regions of the southwestern region of Uzbekistan is of interest to local and foreign researchers because it changes over the seasons and years, yet it is little studied. Valiyev et al (2023), Jurakulov et al (2023), Kudratov et al (2023), Zokirova et al (2022), and Narzullayev (2022; recorded important information about the composition, distribution, and importance of the flora and fauna of this area as a result of their extensive research. At the same time, the degradation of pastures in arid regions is intensifying, as observed all over the world in recent years (Rajabov et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Geographically, one third of the territory of Uzbekistan consists of mountains (Kudratov et al 2023). Sudden changes in the climate in the mountains, the large-scale impact of stress factors on the diversity of flora (Akramov et al 2023;Alikulov et al 2023;Bazarov et al 2023) and fauna (Nurullayeva et al2023;Narzullayev 2022;Khalimov 2023;Khalimov et al 2023;Narzullayev et al 2023) affected. In addition, there is a high possibility that this condition caused the grain quality indicators to differ among agricultural crops, including wheat varieties, which have been cultivated in the mountain region for a long time.…”
Section: Introductionmentioning
confidence: 99%